(untitled) (Research, Society and Development, 2020)
The objective of this research is to analyze the evaluation in Technical Education of Medium Level considering the diversity of identity of the students’ profile. This bibliographic and documentary research uses the qualitative approach methodology. To this end, a detailed search for scientific production was carried out in the Digital Library of Theses and Dissertations (BDTD) and in the CAPES Journal Portal, prioritizing publications on evaluation in professional education. It also contemplated the documentary analysis of the pedagogical projects of the courses of Technical Vocational Education in High Level. From the organization of information and knowledge of the analyzed materials, we identified three categories of analysis: the functions of the evaluation; the assessment instruments; the evaluation criteria. Among the theoretical references with which we dialogue, the following stand out: André & Passos, Sposito, Souza & Silva, Vianna, Dayrell, Carrano & Maia, Dayrell, Depresbiteris, Hadji, among others. The results indicate that the assessment of learning should allow the teacher to have as much information as possible about the students’ development, constituting a guiding strategy of the process, through the various functions that he assumes in the school context. In addition to consisting of different instruments and criteria, it contributes to meeting the profile of professional education students, constituting multiple factors resulting from living conditions and the different experiences they experience in their social and school contexts.